School culture and teachersâ perspectives on Special Education Needs (SEN) and disabilities within Guyanaâs mainstream elementary school system - Lashley, Lidon (Social Science Learning Education Journal, 2017)
This study explored school culture and teachersâ perspectives on Special Education Needs (SEN) and disabilities in relation to the inclusiveness of education within Guyanaâs mainstream elementary school system.It was concluded that Guyanese mainstream elementary teachers have basic general knowledge of the theories and principles of being inclusive and promoting inclusive education. However, they lack training in the area of SEN. They are either unaware or uncertain of whether they have learners in their classes who have SEN that are not physical disabilities or known learning disabilities. Secondly, teachers are biased against teaching learners with SEN because they feel unsupported. They associate learners with SEN with challenging behaviours low cognitive ability and underachievement.Finally, the study proved that there is a direct relationship between school culture and teachers perspectives on SEN and disabilities. This is directly related to the inclusiveness of education within Guyanaâs mainstream elementary schooling system.